Extraction and biomolecular analysis of dermal interstitial fluid collected with hollow microneedles. (December 2018) - Miller, Philip; Taylor, Robert; Tran, Bao; Boyd, Gabrielle; Glaros, Trevor; Chavez, Victor; Krishnakumar, Raga; Sinha, Anupama; Poorey, Kunal; Williams, Kelly; Branda, Steven; Baca, Justin; et al.
Abstract Dermal interstitial fluid (ISF) is an underutilized information-rich biofluid potentially useful in health status monitoring applications whose contents remain challenging to characterize. Here, we present a facile microneedle approach for dermal ISF extraction with minimal pain and no blistering for human subjects and rats. Extracted ISF volumes were sufficient for determining transcriptome, and proteome signatures. We noted similar profiles in ISF, serum, and plasma samples, suggesting that ISF can be a proxy for direct blood sampling. Dynamic changes in RNA-seq were recorded in ISF from induced hypoxia conditions. Finally, we report the first isolation and characterization, to our knowledge, of exosomes from dermal ISF. The ISF exosome concentration is 12–13 times more enriched when compared to plasma and serum and represents a previously unexplored biofluid for exosome isolation. This minimally invasive extraction approach can enable mechanistic studies of ISF and demonstrates the potential of ISF for real-time health monitoring applications. Philip Miller et al. present an approach for extracting dermal interstitial fluid (ISF) using an array of hollow microneedles in a cylindrical substrate that minimizes skin compression and tissue damage. They extract larger volumes of ISF suitable for downstream analyses, compared to previous reports.